Effect of Shallot Biopesticide Extract and Liquid Organic Fertilizer on Plant Growth and Suppression of Fusarium-Induced Twisting Disease - Haryuni Haryuni; Endang Suprapti; Mugi Harsono; Suji Tegar Prasetio; Sindi Suryani; Handung Nuryadi (Biosaintifika: Journal of Biology & Biology Education, 2026)
Shallot (Allium ascalonicum L.) is a major agricultural commodity in Indonesia. This plant contributes significantly to the national economy and contains numerous bioactive compounds with various properties, such as antioxidant, antibacterial, and antifungal activity. However, the biggest production constraint is infection by the pathogen Fusarium, known as Twisting disease. Therefore, this study aimed to investigate the effect of combining biopesticides and liquid organic fertilizer (LOF) in shallot farming on Fusarium spp. The experiment was conducted using randomize block design with two main parameters. The first parameter was the interval of biopesticide extract applications, namely, no extract, once a week, and once every two weeks. The second parameter was the LOF dosage, including 0, 25, 50, and 75 mL/plant. Plant height, number of leaves, fresh biomass, and disease incidence were observed to evaluate the effect of biopesticides and LOF application. The results showed that a combination of biopesticide extract and LOF positively affected growth but suppressed disease incidence. The combination of once-a-week biopesticide extract and 75 mL/plant LOF applications was identified as the best treatment. In conclusion, biopesticide extract and LOF can be applied for sustainable, environmentally friendly disease management in shallot plants. The results support Sustainable Development Goals (SDGs) 2, 12, and 15 by controlling Fusarium fungal infections in shallots, maintaining production, reducing the use of chemical pesticides, and promoting sustainable agricultural management.